The health and economic impact of the Tobacco 21 Law in El Paso County, Texas: A modeling study - Whitney Garney; Sonya Panjwani; Laura King; Joan Enderle; Dara O'Neil; Yan Li (Preventive Medicine Reports, 2022)
In December 2019, the US federal Tobacco 21 (T21) law passed to raise the minimum legal purchase age for tobacco products from 18 to 21 years. Preliminary evidence suggests that the T21 law will restrict youth access to tobacco products, leading to decreases in tobacco use over their lifetime. This study expands the science through the use of systems modeling by linking decreases in youth tobacco use in El Paso County, Texas, due to the T21 law implementation, to potential cardiovascular health (CVH) benefits and health care cost reductions. Using a smoking behavior and cardiovascular disease agent-based model, we projected the T21 law’s long-term effects on smoking prevalence and CVH outcomes in El Paso County, Texas. The estimated smoking prevalence in El Paso County, Texas, decreased by 2.7% among 18–24 year olds and by 5.2% among 25–44 year olds in 20 years with T21 law implementation (p < 0.01 for both population groups). By reducing tobacco use, the T21 law could prevent 5.4 coronary heart disease events per 1,000 adults and 6.1 S events per 1,000 adults over a lifetime. The model estimated a reduction in lifetime health care costs from $42,929 per person without T21 law to $41,985 per person with the policy. This study provides further evidence for policymakers and communities to understand the potential health and economic impacts of the federal T21 law at the local level. Results emphasize the need for comprehensive policy implementation and enforcement to produce its intended impact on health outcomes.